Characterization of Gut Microbiome in the Mussel Mytilus galloprovincialis in Response to Thermal Stress - Li, Yi-Feng; Xu, Jia-Kang; Chen, Yan-Wen; Ding, Wen-Yang; Shao, An-Qi; Liang, Xiao; Zhu, You-Ting; Yang, Jin-Long (Frontiers in Physiology, 2019)
The gut microbiota is essential for utilization of energy and nutrition and may have a role in host immunity in response to environmental shifts. The present study evaluated the temperature stress (increasing from 21°C to 27°C) on gut microbiome and dynamics of the mussel Mytilus galloprovincialis by 16S rRNA gene sequencing with the aim of discovering the gut microbiome resilience to warming. Exposure to high temperature of 27°C significantly reduced the survival of M. galloprovincialis associated with increased microbial diversity of gut. The microbial communities were shifted with elevated temperature (from 21 to 27°C) and different exposure time (from day 0 to day 7) by principal coordinate analysis (PCoA). Linear discriminant analysis effect size (LEfSe) analysis revealed that the relative abundance of Vibrio and Arcobacter presented in live animals as the top genus-level biomarkers during the initial exposure to 27°C and followed by microbiomes fluctuation with increasing exposure time at day 4 and day 7. The proliferation of opportunistic pathogens such as genus Vibrio and Arcobacter might increase host susceptibility to disease and contributed greatly to mortality. The results obtained in this study provide the knowledge on ecological adaptation for south domestication of M. galloprovincialis and host-bacteria interaction during temperature stress (27°C).